Efektifitas Pengampunan Pajak dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak (KPP) Bandar Lampung - Rina Milyati Yuniastuti; Jhon Nasyaroeka; Hesti Widi Astuti (Program Pascasarjana Universitas Gajayana, 2019)
The purpose of this research is to examine the influence of tax amnesty to tax sanction in KPP Bandar Lampung, to examine the influence of tax amnesty of to tax obedience of taxpayer in KPP Bandar Lampung, and to examine the influence of tax sanction to tax obedience of taxpayer in KPP Bandar Lampung. Result shows that the influence of X1 to X2 is statistically significant (0,016 < 0,05), the influence of X1 to Y2 is not statistically significant (0,135 > 0,05) and the influence of X2 to Y2 is statistically significant (0,02 < 0,05). The influence of Y1 to Y2 is found to be statistically significant (0,000 < 0,05). The influence of X1 to Y2 is found to be not statistically significant (0,316 > 0,05).